A study on high-pressure adsorption and desorption of methane, ethane, propane and their mixtures on porous adsorbents - Ridha, Firas Noori (2006)
This work investigates the high pressure adsorption and desorption of methane, ethane, propane and their mixtures on different types of adsorbents in both equilibrium and dynamic systems. A treatment based on thermodynamic concepts was considered to further study the equilibrium system. Meanwhile, a thermodynamic modeling was performed to calculate the experimentally immeasurable adsorption quantities. The results demonstrated that activated carbons provide better adsorption capacities than molecular sieve zeolites and silica gel due to their highly developed porosities. Gas residual amount was observed to be related proportionally to gas molecular weights and bed temperature drop during desorption. Excess adsorption calculated for mixture on the basis of pure gases mole fractions was always higher than that obtained from the mixture within 10-30 % depending on adsorbent and gas mixture properties. This was found to be raised from the competition behavior between dissimilar species in the mixture. Methane maximum discharge rate of 5 L/min resulted in the most severe reduction in steady state delivery capacity, represented by a factor between 8.8-13.5 % compared to that delivered at 1 L/min. This was due to the extremely high temperature drop of –51.3 oC, a net drop of 78.3 oC, corresponding to an increase in drop range of about 40% compared to that at 1 L/min. Ethane and propane have potential impacts on all types of delivery capacities within a reduction factor between 19.4 to 37.1 % for discharge rate of 1 L/min. From the results of this work, it can be concluded that the presence of ethane and propane in the mixture substantially reduced the adsorption of methane. In addition, temperature drop in the dynamic system is unavoidable even when the chamber is discharged at the lowest possible rate, causing an increase in gas retention and consequently loss in storage delivery capacity. The introduction of the nonideality assumption into the conventional Kelvin equation has enhanced the applicability of the equation to describe the capillary condensation of subcritical gases at high pressures